BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA PETANI - Marlinda Putri Hartanti; Mifbakhuddin M (Universitas Muhammadiyah Semarang, 2015)
Backrground. Hypertension is a major public health problem in Indonesia and other developingcountries. Hypertension prevalence in Indonesia is 6,8 % . Farmersin Ringins Villagesusceptible to hypertension, becauseof smooking behavior,consumption coffee, lessexercise andhadless of sodium intake. Objective. To analysecorelation between age, drinking coffee, smoking habbits, exercise habits ands sodium intakewith hypertension inthe Ringins Village, Rembang . Methods. Explanatory research designewithcross sectional approach. Populationsare35farmersand all of them being sample.The independent variablesis age, drinking coffee, smoking habbits, exercise habbits, and consume ofintake sodium. The dependent variableis hypertension. statistical testused is Pearson correlation and Spearman Ranktest are used is this research. Results: most ofrespondents (62,9%) isin middleaged (41 -60years), 42.9% respondents had the habit of drinking coffee, most of respondents (54.3%) had habbit ofnot smoking, majority of respondentshad a habit ofregularexercise (91.4%), most of respondents (54.3%) had less of sodiumintakeandmost of respondents (62.9%) had hypertension. There is significant corelations between consumption cofee with hypertension ( p= 0,015), there is no significant correlations between smoking ( p= 0,709), exercise habits ( p= 0,262) and natrium intake ( p=0,218 ) with hypertension. Conclusion.: There is significant corelations between age, and consumption coffe with hypertension, but no corelation between smoking, exercise habits and natrium intake with hypertension.